Pengaruh Media Magnetic Board Math terhadap Hasil Belajar Siswa Kelas 1 SDN I Dukuhagung Tikung Lamongan - Iin Rosyidatur Rohmah; Sunanto Sunanto; Nafiah Nafiah; Afib Rulyansah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
In learning mathematics there are still many students who think that mathematics is a difficult subject, on average the teacher only uses a lecture strategy which results in students getting bored in the process of learning children's understanding. This study aims to determine the effect of Magnetic Board Math Media before, after and its effect on student learning outcomes in grade 1 SDN I Dukuhagung Tikung Lamongan. This research uses a quantitative approach with a Pre-Experimental design. By using the One Group Pretest-Posttest design. The results of this study indicate that there is an effect of differences in student learning outcomes before and after the Magnetic Board Math Media is applied with an increase in the average Pretest score of 45.01 and for the Posttest it increases with an average of 86.82. So that there is an effect of applying Magnetic Board Math Media to increasing learning outcomes, it is said to be an increasing category. In general, research shows that there is an effect of differences in student learning outcomes before and after applying Magnetic Board Math Media with a Pretest Percentage of 9% and for Posttest it increases with a percentage of 91 %. So that there is an influence of the application of Magnetic Board Math Media on increasing student learning outcomes.